2007
DOI: 10.1136/bmj.39171.637106.ae
|View full text |Cite
|
Sign up to set email alerts
|

Alarm symptoms in early diagnosis of cancer in primary care: cohort study using General Practice Research Database

Abstract: New onset of alarm symptoms is associated with an increased likelihood of a diagnosis of cancer, especially in men and in people aged over 65. These data provide support for the early evaluation of alarm symptoms in an attempt to identify underlying cancers at an earlier and more amenable stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
228
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(244 citation statements)
references
References 24 publications
(22 reference statements)
10
228
1
3
Order By: Relevance
“…However, the risk of a person<60 years old having malignancy is typically very low so, even with an alarm feature, the risk is still much <1% and it is very unlikely that endoscopy of all young patients with alarm features would be cost-eff ective. Data published since this systematic review have been administrative database studies that have confi rmed that alarm features have a low positive predictive value and so are of limited value in stratifying patients for endoscopy (34)(35)(36)(37). It should be noted that this guideline does not cover patients presenting with alarm features such as progressive dysphagia and/or weight loss in the absence of epigastric pain.…”
Section: Conditional Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…However, the risk of a person<60 years old having malignancy is typically very low so, even with an alarm feature, the risk is still much <1% and it is very unlikely that endoscopy of all young patients with alarm features would be cost-eff ective. Data published since this systematic review have been administrative database studies that have confi rmed that alarm features have a low positive predictive value and so are of limited value in stratifying patients for endoscopy (34)(35)(36)(37). It should be noted that this guideline does not cover patients presenting with alarm features such as progressive dysphagia and/or weight loss in the absence of epigastric pain.…”
Section: Conditional Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…Furthermore, the 2-week rule did not appear to identify patients at earlier stages of cancer (4). Although the United Kingdom's "2-week rule" example did not show unequivocal success, based on this initial experience, this health system is now likely better equipped to evaluate the structureprocess-outcomes and make the necessary changes.…”
Section: From a Supplement Authormentioning
confidence: 92%
“…To our knowledge, the largest study to address the question of frequency of alarm symptoms in general medical settings and their likelihood of cancer was conducted by Jones et al (4). The study found that while patients commonly presented to their primary care providers with symptoms, such as hematuria, hemoptysis, dysphasia, and rectal bleeding, more than 90% of the patients did not have cancer (Table 1).…”
mentioning
confidence: 99%
“…An open cohort of patients aged 30-84 years was identified, drawn from patients registered with practices between 1 January 2000 and 30 September 2010. The following were excluded: patients without a postcoderelated Townsend score, those with a history of pancreatic cancer at baseline, and those with a recorded red flag symptom 13 in the 12 months prior to the study entry date. For this study, a red-flag symptom was defined as one that might alarm the patient and indicate the presence of pancreatic cancer, that is, symptoms of dysphagia, loss of appetite, weight loss, abdominal pain, or abdominal distension.…”
Section: Study Design and Data Sourcementioning
confidence: 99%